CULTURAL, POLITICAL AND ECONOMIC ASPECTS OF THE INTERNATIONAL EXPANSION OF BANKS FROM CENTRAL AND EASTERN EUROPE – CASES: POLISH PKO BP AND HUNGARIAN OTP BANK - Kurkliński, Lech (Acta Universitatis Lodziensis. Folia Oeconomica, 2014)
Polish PKO BP and Hungarian OTP Bank are the largest, dominant national banking institutions of a similar nature – universal banks with a strong emphasis on retail operations. However, they differ significantly because of international activities. PKO BP has only local bank in Ukraine, and the OTP group is present in 9 countries in CEE. The relatively strong economic position of both banks, similar history would indicate that their activities related to foreign expansions should develop in the same way. However, this hasnʼt happen. Among a number of reasons we should include cultural aspects, closely bound up with the legacy of the past, political and economic circumstances for both countries.